2018
DOI: 10.1016/j.molimm.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG lacking effector functions demonstrate lower FcRn-binding and reduced transplacental transport

Abstract: We have previously generated human IgG1 antibodies that were engineered for reduced binding to the classical Fcγ receptors (FcγRI-III) and C1q, thereby eliminating their destructive effector functions (constant region G1Δnab). In their potential use as blocking agents, favorable binding to the neonatal Fc receptor (FcRn) is important to preserve the long half-life typical of IgG. An ability to cross the placenta, which is also mediated, at least in part, by FcRn is desirable in some indications, such as feto-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Likewise, deglycosylated IgGs were transported in mice [ 84 ]. Furthermore, a comparison of glycosylation patterns between fetal and maternal IgG by Stapelton et al in 2018 concluded that IgG transport was not glycosylation selective [ 85 ]. Regardless, the differences in permeation rate between WT and DG IgG, together with the differential transport of IgG subclasses described in several studies, suggests that there is at least one factor X involved in IgG transport in the nasal mucosa in addition to FcRn [ 61 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, deglycosylated IgGs were transported in mice [ 84 ]. Furthermore, a comparison of glycosylation patterns between fetal and maternal IgG by Stapelton et al in 2018 concluded that IgG transport was not glycosylation selective [ 85 ]. Regardless, the differences in permeation rate between WT and DG IgG, together with the differential transport of IgG subclasses described in several studies, suggests that there is at least one factor X involved in IgG transport in the nasal mucosa in addition to FcRn [ 61 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently generated a IgG variant lacking Fc-receptor effector functions by engrafting IgG2- and IgG4-derived amino acids onto IgG1 (Δnab 35 ), which still binds FcRn. However, this variant showed surprisingly low FcRn-mediated transport 36 , warranting further investigation. Here we present a study on FcRn mediated IgG1 and IgG2 transcytosis and describe new findings on the differential transport of these subclasses.…”
Section: Introductionmentioning
confidence: 90%
“…Of the four IgG subclasses IgG1 and IgG4 are transported readily, whereas IgG2 and IgG3 show somewhat less efficient transplacental passage (28, 142, 143). In ex vivo human placenta transport studies, model IgG molecules disabled in FcRn binding did not cross to the fetal circulation (66, 144), while, conversely, an IgG variant with improved affinity for FcRn was transported more efficiently (145). Also, polarized human trophoblast-derived BeWo cells exhibited apical to basolateral IgG transcytosis and apical IgG recycling (146).…”
Section: Functional Consequence Of Fcrn Expression In Epitheliummentioning
confidence: 99%